Determination Of Hopelessness Levels Of Final Year Students Of The Faculty Of Medicine - Kaygusuz, Türkkan; Erensoy, Ahmet (My University, 2020)
Background: Hopelessness, which includesboth the characteristics of depressionand anxiety, is thought to be triggered byenvironmental stress. In case of hopelessness,emotional disorders, despair and inability tosolve problems arise. This study was conductedto determine the level of hopelessness of thefinal year students in medical school and todetermine whether there is a difference in thelevels of hopelessness according to gender andage variables.Methods: A total of 124 medical faculty lastyear students, 60 of them (48.4%) male,were included in this study. Using the Beck’sHopelessness Scale Score, the hopelessnesslevels of the students and the three major aspectsof hopelessness, i.e. feelings and expectationsabout the future, loss of motivation and hopesabout the future were evaluated.Findings: The mean Beck’s HopelessnessScale Score of the students was 6.29. 30.6%of the students had no hopelessness, 48.4%had mild hopelessness, 13.7% had moderatehopelessness and 7.3% had severe hopelessness.No statistically significant difference was foundbetween gender and age groups. For the studentswho preferred medical school to serve humanity,the mean Beck’s Hopelessness Scale Score weresignificantly lower than those who did not preferfor this purpose; Beck’s Hopelessness ScaleScore means were found to be significantlyhigher for those who preferred to earn moremoney. While the majority of the students (89%)did not have any professional future concerns,it was found that the Beck’s Hopelessness ScaleScore mean was significantly higher in studentswho were concerned about not being able toearn enough in the future.Conclusion: It was found that the students’feelings and expectations about the future werenot negative, the loss of motivation was notsignificant and the hopes about the future werequite high.
Keywords: Genel ve Dahili Tıp; Psikoloji